2014
DOI: 10.1089/chi.2014.0017
|View full text |Cite
|
Sign up to set email alerts
|

Fruits and Vegetables Displace, But Do Not Decrease, Total Energy in School Lunches

Abstract: Background: The high overweight and obesity prevalence among US children is a well-established public health concern. Diet is known to play a causal role in obesity. Increasing fruit and vegetable (FV) consumption to recommended levels is proposed to help reduce obesity, because their bulk and low energy density are believed to reduce energy-dense food consumption (volume displacement hypothesis). This study tests this hypothesis at the lunch meal among upper-elementary students participating in a Farm to Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…The average number of schools sampled was 7.7 (standard deviation, 11.1; range, 1–60). Of studies conducted in more than one school (35 studies), 15 studies ( 18 , 20 – 22 , 25 , 38 , 41 , 45 , 46 , 49 , 50 , 53 , 57 , 60 , 64 ) reported using a statistical method that accounted for clustering. Most studies (30 studies) sampled from schools in which more than half of students were eligible for free or reduced-price lunch; 7 studies did not report this characteristic ( 26 , 28 , 32 , 35 , 52 , 54 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average number of schools sampled was 7.7 (standard deviation, 11.1; range, 1–60). Of studies conducted in more than one school (35 studies), 15 studies ( 18 , 20 – 22 , 25 , 38 , 41 , 45 , 46 , 49 , 50 , 53 , 57 , 60 , 64 ) reported using a statistical method that accounted for clustering. Most studies (30 studies) sampled from schools in which more than half of students were eligible for free or reduced-price lunch; 7 studies did not report this characteristic ( 26 , 28 , 32 , 35 , 52 , 54 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…The methods used to assess fruit and vegetable consumption varied: 19 studies used weighed plate waste ( 16 , 24 , 30 , 32 , 34 – 37 , 40 42 , 44 , 45 , 50 , 52 , 56 , 58 , 60 , 64 ), 15 studies used direct observation ( 17 , 25 – 27 , 29 , 31 , 33 , 39 , 46 , 47 , 54 , 56 , 57 , 59 , 63 ), 12 studies used digital photography ( 18 – 20 , 22 , 23 , 28 , 48 , 49 , 52 , 55 , 61 , 62 ), and 4 studies used a self-report instrument that included 24-hour recalls, food records, or questionnaires ( 21 , 38 , 43 , 51 ). On average, studies collected data on fruit and vegetable consumption across a total of 23 school days; the mode for duration of data collection was 5 days.…”
Section: Resultsmentioning
confidence: 99%
“…The purposes of each study varied, with food waste measures aimed at primarily understanding the amount of food waste 22 , 31 and food consumption, 25 , 27 , 28 modification of food environment or lunchtime procedures, 26 , 29 instrument validity, 23 compliance with nutrition recommendations, 24 and nutrition education. 30 , 32 Studies were conducted in the West, 25 , 26 Midwest, 27 , 28 , 30 , 31 Northeast, 29 and South, 22 , 24 , 32 although one did not report geographic location. 23 Alaimo and colleagues 30 and Monlezun and colleagues 32 reported free and reduced rates near 100%, whereas several other studies did not report free and reduced rates.…”
Section: Resultsmentioning
confidence: 99%
“… 25 , 27 , 29 Several studies expressed food waste in terms of calories rather than as a percentage of food wasted. 26 , 28 , 32 …”
Section: Resultsmentioning
confidence: 99%
“…For example, greater variety of foods higher in energy density (high-energy-dense [HED] foods) may increase intake of these foods, contributing to greater overall energy intake. Alternatively, greater variety of foods lower in energy density (low-energy-dense [LED] foods) may increase intake of these foods, and due to their energy density may not significantly increase energy intake, or may actually assist with reducing energy intake if increased consumption of LED foods reduces intake of HED foods due to the occurrence of substitution or displacement [44].…”
Section: Historical Context and Theoretical Basis For Defining Varietymentioning
confidence: 99%